2017
DOI: 10.1111/maec.12369
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and phylogeography of the land hermit crab Coenobita purpureus (Decapoda: Anomura: Coenobitidae) in the Northwestern Pacific Region

Abstract: Hermit crabs of the family Coenobitidae comprise the land hermit crabs, with 16 Coenobita species, and the coconut crab Birgus latro. They are terrestrial but spend their marine life as planktonic larvae. Some coenobitid crabs are widely distributed in the Indo‐West Pacific region, and some species occupy narrower ranges. To improve our knowledge of coenobitid crab speciation and geographical distribution patterns, we examined the phylogenetic relationship between Coenobita purpureus, which has a narrow distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Although significant interspecific differences were found in the egg sizes of the 6 coenobitids, as previously shown for C. cavipes, C. purpureus and C. rugosus by Nakasone (2001), egg size did not affect embryonic development, such as the LTT and ECT values. Hamasaki et al (2016) examined the phylogenetic relationships among 7 coenobitid species based on 16S rDNA se quences. They found that B. latro branched off from the outer diogenids (sister marine hermit crabs) first, followed by C. brevimanus, and that the other species comprised 3 clusters: (1) C. cavipes and C. perlatus H. Milne-Edwards, 1837, (2) C. violascens, and (3) C. rugosus and C. purpureus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although significant interspecific differences were found in the egg sizes of the 6 coenobitids, as previously shown for C. cavipes, C. purpureus and C. rugosus by Nakasone (2001), egg size did not affect embryonic development, such as the LTT and ECT values. Hamasaki et al (2016) examined the phylogenetic relationships among 7 coenobitid species based on 16S rDNA se quences. They found that B. latro branched off from the outer diogenids (sister marine hermit crabs) first, followed by C. brevimanus, and that the other species comprised 3 clusters: (1) C. cavipes and C. perlatus H. Milne-Edwards, 1837, (2) C. violascens, and (3) C. rugosus and C. purpureus.…”
Section: Discussionmentioning
confidence: 99%
“…This crab is also found on the Pacific coasts of mainland Japan (< 35° N) (Hamasaki et al 2016). Additionally, several widely distributed coenobitids, including Coenobita brevimanus Dana, 1852, C. cavipes Stimpson, 1858, C. rugosus H. Milne-Edwards, 1837, C. violascens Heller, 1862 occur in the southern oceanic islands, Japan (Nakasone 1988, 2001, Hamasaki et al 2016.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terrestrial hermit crabs belong to the family Coenobitidae of Anomura, which includes only two genera: the land hermit crab genus Coenobita, with 16 species, and the coconut crab genus Birgus, with only one species, B. latro [ 21]. Nevertheless, it has been indicated that among the 16 Coenobita species, C. carnescens could be in fact the juvenile form of C. perlatus, and that C. olivieri is only a variety of C. spinosus [ 22,23]. It has been proved that complete mitogenome is common used for species identification, especially for the controversial classifications which possess similar morphology.…”
Section: Introductionmentioning
confidence: 99%
“…1). While the current is sufficiently powerful to potentially impact larval gene flow in some marine organisms (Kawabe, 1986;Sugimoto & Kobayashi, 1988;Tomita et al, 2016;Abdullah et al, 2017;Hamasaki et al, 2017), it has also been demonstrated to act as a potential genetic barrier to dispersal in other marine species (Aoki et al, 2008a;Iwamoto et al, 2012;Imai et al, 2013;Yamakawa & Imai, 2014;Iwamoto et al, 2015). Results here at least suggest that the Kuroshio Current potentially limits larval dispersal by fiddler crabs between the Seto Inland Sea and Kyushu regions.…”
Section: Significant Differentiation Between Localitiesmentioning
confidence: 99%